Entrepreneurial competencies, organizational structure and SMEs performance in Malaysia : the role of innovation as a moderator - Mohd Sufli, Yusof (2018)
Small and Medium Enterprises (SMEs) receive great attention on its contributions in the policies of economic and social development either in the developed or in developing countries like Malaysia. However, there has not been much research focuses on performance of SMEs in Malaysia especially in manufacturing sector. This study investigates the factors that affect performance of manufacturing SMEs in the Malaysian economy. Specifically, the purpose of this study is to examine moderating effect of innovation on SMEs performance and its relationship with traits competencies, skills competencies and organization structure in Northern Malaysia. A survey methodology has been employed to collect the data. SMEs owners and managers throughout the northern states of Malaysia are chosen as the samples for this study. A disproportionate simple stratified random sampling method was used to select respondents from the respective owners and managers. Seven hypotheses were proposed regarding SMEs performance. Structured questionnaires were used to measure five variables; SMEs performance, traits competencies, skills competencies, organization structure and innovation are adopted in this study. Out of 800 questionnaires that were filled by respondents on the “drop and collect” basis, only 314 were usable, yielding a response rate of 39.25%. The findings revealed that significant relationships exist among variables (traits competencies, skills competencies, organization structure and innovation with SME performance. The findings also revealed that innovation moderates the relationships between traits competencies, skills competencies and organization structure on SME performance. The study concludes with a discussion on theoretical and practical implications and suggestions for future research.